Blood world - Mooney, Chris (Berkley, 2020)
"A drug that makes the blood of carriers a fountain of youth, a psychopath who doesn't care how many bodies he leaves in his wake, and an LAPD detective hopelessly compromised by a dark secret. Together, they're an explosive mix that's going to shatter the city of Los Angeles into a million corpuscles. The most valuable commodity on earth is the blood of "carriers." These young people hold within them a virtual fountain of youth. Those with the right genes produce blood that, when treated with a new wonder drug, cures disease, increases power, and makes the recipient a virtual superman. It also makes the carriers targets. Blood farms filled with kidnapped children spring up around the country, and Los Angeles is at the center of this blood-dealing world. The police are overwhelmed. Ellie Bautista became an LAPD officer specifically to fight this evil as a member of the Blood Squad, but she has been consistently denied a transfer to the prestigious unit--until the day she and her partner are ambushed during a routine stop. The resulting events plunge her into an undercover world more dangerous than she could have ever imagined. A madman has found a way to increase the potency of the blood to levels previously unimagined. As he cuts a bloody swath through the already deadly world of blood cartels, Ellie is the only hope to stop him before the body count rises"--